Number of repetitions performed in different exercise order in upper-body resistance training - Teixeira, André (2013)
The aim of this study was to compare the number of repetitions performed with different exercise order for the back and biceps muscles in resistance training. For this, 11 trained subjects (23.7 ± 3.7 years, 67.7 ± 6.4 kg, 171.4 ± 5.9 cm) performed the 1RM test and retest. After, participants performed randomly two different exercise order: a) Lat pull down and biceps curl (LPD/BC); b) Biceps curl and lat pull down (BC/LPD). The tests were conducted in three maximum sets with 70% of 1RM and two minutes rest interval between sets. There were no significant differences in the number of repetitions between exercises in all sets regardless of the exercise order (p<0.05). In addition, no significant differences occurred in the total volume of repetitions between the different exercise order (LPD/BC: 66.7 ± 8.9 repetitions; BC/LPD: 68.2 ± 5.1 repetitions) (p=0.395). In conclusion, the exercise order did not affect the number of repetitions performed during resistance training for back and biceps muscles.